Intracranial pressure during hemodialysis in patients with acute brain injury. Issue 4 (3rd December 2018) - Lund, Anton; Damholt, Mette B.; Wiis, Jørgen; Kelsen, Jesper; Strange, Ditte G.; Møller, Kirsten
Abstract : Background: Because osmotic fluid shifts may occur over the blood‐brain barrier, patients with acute brain injury are theoretically at risk of surges in intracranial pressure (ICP) during hemodialysis. However, this remains poorly investigated. We studied changes in ICP during hemodialysis in such patients. Methods: We performed a retrospective study of patients with acute brain injury admitted to Rigshospitalet (Copenhagen, Denmark) from 2012 to 2016 who received intermittent hemodialysis (IHD) or continuous renal replacement therapy (CRRT) while undergoing ICP monitoring. Data from each patient's first dialysis session were collected. Area under the curve divided by time (AUC/ t ) for ICP was calculated separately before and during dialysis. Results: Thirteen patients were included. During dialysis, ICP increased from a baseline of 11.9 mm Hg (median; interquartile range 6.3‐14.7) to a maximum of 21 mm Hg (18‐27) ( P  = 0.0024), and AUC/ t for ICP was greater during dialysis (15.2 (13.4‐18.8) vs 11.7 mm Hg (6.4‐15.1), P  = 0.042). The maximum ICP increase was independent of dialysis modality, but peak values were reached earlier in patients treated with IHD (N = 4) compared to CRRT (N = 9) (75 [30‐90] vs 375 min [180‐420] after start of treatment, P  = 0.0095). The maximum ICP increase correlated positively to the baseline plasma urea concentration (Spearman's r  = 0.69, P  = 0.017). Conclusion: Hemodialysis is associated with increased ICP in neurocritically ill patients, and the magnitude of the increase may be related to initial plasma urea levels.